HUBUNGAN ABSENT MINDED SCROLLING DENGANPROKRASTINASI AKADEMIK PADA MAHASISWA - Innaya Dinda Syafira; Rahayu Hardianti Utami (Departemen Psikologi, Universitas Negeri Padang, 2025)
The purpose of this study was to examine the correlation between absent-minded scrolling and academic procrastination among 2022-2024 batch students at Universitas Negeri Padang. A total of 310 participants were selected for this study through purposive sampling method. In this study, the academic procrastination scale was measured using the Tuckman Procrastination Scale (TPS) scale, which had been adapted by Kurniati, while the Absent-Minded Scrolling scale was measured using the Smartphone Use Questionnaire scale: Absent-Minded (SUQ-A) scale adapted by researchers from Marty-Dugas which has been developed by Antonie Eid. Data analysis using the Spearman Rank correlation test, with the help of IBM SPSS Statistics 25 for Windows. The findings show that there is a relationship between absent minded scrolling and academic procrastination in Padang State University students from 2022 to 2024. This is proven by the results of the Spearman test which shows a coefficient value of 0.540 and a significance value of 0.000 which indicates a positive relationship between mindless scrolling behavior and delays in completing academic tasks. These results further suggest that an increase in absent-minded scrolling is associated with an increase in academic procrastination among Universitas Negeri Padang students from the batches of 2022 to 2024. Thus, it can be concluded that the alternative hypothesis (H1) is supported, while the null hypothesis (H0) is not supported.